2018
DOI: 10.1017/s0022215118000671
|View full text |Cite
|
Sign up to set email alerts
|

Provision of physiotherapy rehabilitation following neck dissection in the UK

Abstract: The provision of physiotherapy is most commonly reactive rather than proactive, and usually driven by patient request. There is little evidence of pre-arranged physiotherapy for patients to treat or prevent shoulder dysfunction in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Acting more proactively by providing good access to physiotherapy treatment early after, or alongside, breast cancer treatment could help to reduce the number of people with cancer (or a history of cancer) presenting with musculoskeletal complications. 48 Although our physiotherapist-participants felt very comfortable with aspects of the intervention such as improving shoulder mobility, they expressed a need for greater training, support and guidance in relation to specific issues such as cording and lymphoedema. The physiotherapists delivering the PROSPER intervention were musculoskeletal specialists with limited experience in treating individuals with breast cancer in the acute postoperative period.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Acting more proactively by providing good access to physiotherapy treatment early after, or alongside, breast cancer treatment could help to reduce the number of people with cancer (or a history of cancer) presenting with musculoskeletal complications. 48 Although our physiotherapist-participants felt very comfortable with aspects of the intervention such as improving shoulder mobility, they expressed a need for greater training, support and guidance in relation to specific issues such as cording and lymphoedema. The physiotherapists delivering the PROSPER intervention were musculoskeletal specialists with limited experience in treating individuals with breast cancer in the acute postoperative period.…”
Section: Discussionmentioning
confidence: 96%
“…Physiotherapists in the UK receive little training in rehabilitation following cancer treatment, reflected by the limited centres across the UK with physiotherapists specialised in oncology. 48 Given the increasing number of people surviving cancer and living with the consequences of cancer treatment, there is an urgent need in the UK to upskill physiotherapists in cancer-related rehabilitation to allow people with breast cancer better access to this type of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Currently, there is no national standard best practice for rehabilitation following HNC. Our study development work 16 and feedback from patient and public involvement (PPI) representatives has shown that physiotherapy practice varies across the UK. The findings suggested that rehabilitation in the form of physiotherapy is not routinely available to patients with HNC, in either inpatient or outpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggested that rehabilitation in the form of physiotherapy is not routinely available to patients with HNC, in either inpatient or outpatient settings. 16 When rehabilitation is offered it is often not evidence based, and targets acute respiratory care, ROM exercises for the neck and shoulder, and advice on positioning of the upper limb and shoulder girdle. 15 A booklet may be provided to supplement this treatment.…”
Section: Introductionmentioning
confidence: 99%
“…7 A recently published survey, of nine regional centres across the UK, revealed that the provision of post-operative physiotherapy is not standardised; it is provided in the majority of centres only when significant dysfunction is found, and was not available at all in 11 per cent of centres. 8…”
Section: Introductionmentioning
confidence: 99%